2001
DOI: 10.1001/archinte.161.11.1393
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopy for Acute Nonvariceal Upper Gastrointestinal Tract Hemorrhage: Is Sooner Better?

Abstract: The overwhelming majority of existing data suggest that early endoscopy is safe and effective for all risk groups. The clinical and economic outcomes of early endoscopy should be confirmed in additional well-designed randomized controlled trials. Given the strength of the evidence, efforts to develop a more standardized and time-sensitive approach to acute nonvariceal upper gastrointestinal tract hemorrhage should be undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
2
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(98 citation statements)
references
References 36 publications
5
86
2
5
Order By: Relevance
“…The rebleeding rate observed in our patients (3.4%) was similar to that observed in the Italian PNED study (3.2%) and in other recent publications (17,18), but it was significantly lower than that reported in the Canadian RUGBE study (14.1%) (3,5,8). The divergence of our results from the ones of the Canadian study may be explained because a higher proportion of our patients received combined endoscopic therapy (adrenaline injection plus BICAP) than in the Canadian study; combined therapy has been shown to be superior to pharmacologic treatment for reduction of rebleeding in controlled trials (25)(26)(27). In addition, rebleeding was found to be an independent predictor of death in our study as equal as it has been described in other studies.…”
Section: Discussioncontrasting
confidence: 68%
“…The rebleeding rate observed in our patients (3.4%) was similar to that observed in the Italian PNED study (3.2%) and in other recent publications (17,18), but it was significantly lower than that reported in the Canadian RUGBE study (14.1%) (3,5,8). The divergence of our results from the ones of the Canadian study may be explained because a higher proportion of our patients received combined endoscopic therapy (adrenaline injection plus BICAP) than in the Canadian study; combined therapy has been shown to be superior to pharmacologic treatment for reduction of rebleeding in controlled trials (25)(26)(27). In addition, rebleeding was found to be an independent predictor of death in our study as equal as it has been described in other studies.…”
Section: Discussioncontrasting
confidence: 68%
“…A variety of observational studies and a few randomized trials have assessed this issue, but marked variations in study design, defi nitions, end points, and methodologic rigor make synthesis of the results diffi cult. Two systematic reviews summarize these studies ( 33,34 ).…”
Section: Recommendationsmentioning
confidence: 99%
“…However, observational studies do not document a benefi t in clinical outcomes of endoscopy performed within 2 -12 h of presentation ( 33,34 ). Observational studies do suggest a benefi t of endoscopy within 24 h aft er admission in terms of decreased length of stay ( 35,36 ) and surgical intervention ( 35 ).…”
Section: Recommendationsmentioning
confidence: 99%
“…It favorably affects recurrent bleeding, the need for surgery, and, probably, survival [1][2][3][4]. The question of whether endoscopie hemostasis should be performed early after hospital admission has also been examined in randomized trials [5,6], in observational cohort studies [7][8][9], and in a systematic review [10], and these papers have described early endoscopy as advantageous. However, it is difficult the Baylor bleeding score and the Rockall score), and differed only in the treatment they received.…”
mentioning
confidence: 99%